2015
DOI: 10.18632/oncotarget.3827
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MARCKS phosphorylation contributes to unresponsiveness of breast cancer to paclitaxel treatment

Abstract: Accumulating evidence has suggested that myristoylated alanine-rich C-kinase substrate (MARCKS) is critical for regulating multiple pathophysiological processes. However, the molecular mechanism underlying increased phosphorylation of MARCKS at Ser159/163 (phospho-MARCKS) and its functional consequence in neoplastic disease remain to be established. Herein, we investigated how phospho-MARCKS is regulated in breast carcinoma, and its role in the context of chemotherapy. In a screen of patients with breast tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…18,19,2224,27 Recent studies have indicated that an important function of MARCKS is to provide PI3K with PIP2 pools and thereby activate AKT. 23,27,42 Although the contribution of MARCKS has already been characterized in a handful of solid tumors, most notably carcinomas of the lung, 23,2729 a role has yet to be demonstrated in kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,2224,27 Recent studies have indicated that an important function of MARCKS is to provide PI3K with PIP2 pools and thereby activate AKT. 23,27,42 Although the contribution of MARCKS has already been characterized in a handful of solid tumors, most notably carcinomas of the lung, 23,2729 a role has yet to be demonstrated in kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28,42 Such a dual contribution of MARCKS may explain why an upregulation of MARCKS would not necessarily contribute to tumorigenesis, 20,32 whereas an increase in MARCKS phosphorylation would. 22,23,26 By reducing MARCKS phosphorylation and trapping PIP2 pools at the membrane, MPS effectively inactivates the PI3K/AKT pathway. 23,42 Although treatment with MPS peptide provides a proof-of-concept that targeting MARCKS controls RCC cell growth and regorafenib efficacy, the off-target effects of this peptide in kidney cancer in vivo is an important line of investigation for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was additionally involved in 12-O-tetradecanoylphorbol-13-acetate-mediated migration of neuroblastoma cells (18). It has previously been suggested that elevated MARCKS phosphorylation contributes to the unresponsiveness of breast cancer to paclitaxel treatment (19). The present study hypothesized that MARCKS was the precise intracellular target of miR-34c-3p by using the miRanda, TargetScan and Pictar databases.…”
Section: Discussionmentioning
confidence: 99%
“…MARCKS, originally identified as a major target of protein kinase C (PKC), is a key regulatory molecule regulating actin dynamics [27]. Recently, it has been shown to play a fundamental role in mediating chemoresistance of breast and lung cancer [28, 29]. There are limited studies examining MARCKS in EOC metastasis.…”
Section: Introductionmentioning
confidence: 99%